2017
DOI: 10.1093/cid/cix1068
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Therapeutic Impact of the Timing of Antiretroviral Therapy in Patients Diagnosed With Primary Human Immunodeficiency Virus Type 1 Infection

Abstract: Antiretroviral therapy initiated during PHI promotes long-term reduction of HIV reservoir size. In patients with sustained virologic suppression, inflammation may be driven by non-HIV-related factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
3
22
1
Order By: Relevance
“…4B to D) (30,(56)(57)(58). Also consistent with the findings of previous studies of the present (20,30) and other (17,18,59) copies HIV DNA/million cells in MAA ϩ versus MAA Ϫ participants, respectively; P ϭ 0.0045; Fig. 4E).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…4B to D) (30,(56)(57)(58). Also consistent with the findings of previous studies of the present (20,30) and other (17,18,59) copies HIV DNA/million cells in MAA ϩ versus MAA Ϫ participants, respectively; P ϭ 0.0045; Fig. 4E).…”
Section: Resultssupporting
confidence: 91%
“…It is now well established that early cART initiation limits the latent HIV reservoir size (16)(17)(18)(19)(20) and that the set-point viral load and duration of viral suppression on cART represent additional positive and negative correlates of reservoir size, respectively (21). Immunological factors also play a role.…”
mentioning
confidence: 99%
“…We did not observe any sex‐related difference in long‐term levels of total HIV DNA under ART, contrary to two cross‐sectional studies that reported lower levels in women [14,15]. Most of participants of these studies were chronic initiators, whereas ART initiated during AHI is a major determinant of viral reservoir reduction [16,56‐58]. Here, HIV persistence was evaluated by measure of total HIV DNA in peripheral blood.…”
Section: Discussioncontrasting
confidence: 63%
“…Finally, recent reviews have highlighted the lack of data on sex‐related differences in the establishment and size of the viral reservoir [6,12]. Previous studies have described lower total HIV DNA in women than in men in the first months after infection [13] and under long‐term suppressive ART [14‐16] but no study has assessed it longitudinally.…”
Section: Introductionmentioning
confidence: 99%
“…Given that reservoir establishment begins shortly after infection and continues as long as viral replication remains uncontrolled [11][12][13], timely viremia suppression with combination antiretroviral therapy (ART) should, in theory, limit reservoir complexity. The observation that early ART limits HIV reservoir size in both adult [14][15][16] and pediatric [17][18][19][20] infection supports this; as do the observations that proviral landscapes in elite controllers and early-treated individuals tend to be more homogeneous than viremic controllers and individuals who initiated ART in chronic infection, respectively [5,21,22]. However, the effect of uncontrolled viremia duration on reservoir diversity in individuals who did not initiate early suppressive ART remains unclear.…”
Section: Introductionmentioning
confidence: 73%